Increasing Student Learning Activities in Social Studies through the Syndicate Group Method - Kurniawan, Muchammad Akbar; Amin, Saiful; Dewi, Sari (Program Studi Pendidikan IPS Unesa, 2024)
This study aims to implement the syndicate group discussion approach to enhance the learning engagement of seventh-grade students in Social Studies (IPS), specifically on the topic of socio-cultural issues, at MTs Almaarif 01 Singosari. The method employed is classroom action research (CAR), utilizing field notes and observation sheets for data collection. The data gathered were analyzed descriptively to evaluate the changes occurring in the learning process. The results of the study indicate that the syndicate group discussion approach is effective in improving students' activity and learning outcomes. This effectiveness is evidenced by a significant increase in the average student score, which rose by 23.61 points from the first cycle to the second. This approach enables students to actively engage in discussions, enhance critical thinking skills, and deepen their understanding of the material. Based on these findings, it is recommended that teachers focus more on classroom management, including effectively utilizing learning analysis and controlling discussion time to optimize the learning process. Additionally, it is crucial for teachers to ensure that every group member has an opportunity to contribute, ensuring the success of this approach is evenly distributed among all students.